The effectiveness of Hybrid Learning in Character Building of Integrated Islamic Elementary School Students during the COVID -19 Pandemic - Trisni Handayani; Novelia Utami (Universitas Negeri Makassar, 2020)
In the midst of the COVID-19 pandemic that has hit the world, it has an impact on various sectors, including the education sector so that the learning process continues in shaping the character of the nation's children. The government provides a distance education policy, but in reality there are many obstacles. Teachers can continue to carry out learning with a hybrid learning model, it is hoped that character building will still be instilled. The purpose of this study was to determine the effectiveness of hybrid learning in character building of students at Raudhatul Muttaqin Islamic Elementary School, Bekasi. The research method used is mixed methods with quantitative and qualitative analysis. Based on the results of data analysis, research findings indicate that character building is still instilled with parental guidance and reporting to school in the form of an electronic Learning Management System then validated by the teacher. Face-to-face effectiveness of 90.5%, online 70.6%, and adequate infrastructure 82% character building can still be applied even with hybrid learning. This shows the important role of parents at home is very high. Further research is needed so that the strengthening of character education can continue to be realized even with various approaches